Peran Dewan Kehormatan Penyelenggara Pemilu dalam Menjaga Kemandirian dan Integritas Pemilihan Umum di Indonesia - Dyan Puspitasari (Lentera Hukum, 2018)
Nowadays, Indonesia remains challenged to the barrier in means of transportation, especially in small areas in which it makes arduous the Election Organizers Honorary Council (DKPP) to carry out its duties. Based on Article 25 of DKPP Regulation Number 2 of 2012, one of the facilities provided to DKPP is the implementation of a long-distance trial by video conference. There are a number of challenges faced by DKPP, including the relatively new age so that people do not really know this institution. In addition, the DKPP institution is quite limited to being located only in the capital, while the task of the institution encompasses national jurisdiction. The geographical condition of Indonesia is broad and consists of many areas also make the response to ethics code violations less efficient along with issues of compliance with DKPP decisions. Thus, the role of the DKPP is needed in maintaining the independence and integrity of the organizers of the General Elections (Elections) and ways to strengthen the role of the DKPP in maintaining the independence and integrity of election administration in Indonesia. Keywords: Election Law, Electoral Institution, Independence